Northwest Territories and Yukon Territory - Canada. Department of Mines and Technical Surveys (Department of Mines and Technical Surveys Canada, 1959)
This is a general map of Northern Territories and Yukon in 1959 showing roads, railways, lakes, rivers, cities and towns. "MCR 36" Scale 1:4,000,000, or 63.13 miles to 1 inch. Relief shown by spot heights. Lambert conical projection. Shows roads, railways, lakes, rivers, cities and towns. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .